2018
DOI: 10.1007/s13258-018-0725-x
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic balance of histone acetylation and deconstruction of repressive chromatin marker H3K9me3 during adipocyte differentiation of 3T3-L1 cells

Abstract: Background Adipocyte differentiation is completed by changing gene expression. Chromatin is closely related to gene expression. Therefore, its structure might be changed for adipocyte differentiation. Mouse 3T3-L1 preadipocytes have been used as a cell model to study molecular mechanisms of adipogenesis. Objective To examine changes of chromatin modification and expression of histone modifying enzymes during adipocyte differentiation. Methods Microscopic analysis and Oil Red O staining were performed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…3C). Previous studies have reported on the elevated expression of these histone HATs in the context of adipogenesis, wherein they play crucial roles in the activation of PPARγ and C/EBPα pathways [40,41]. In brown preadipocytes, the loss of GCN5/PCAF hinders adipogenesis by suppressing the expression of PPARγ and PRDM16, indicating the probable involvement of H3K9 acetylation in white adipose tissue browning [42].…”
Section: Discussionmentioning
confidence: 96%
“…3C). Previous studies have reported on the elevated expression of these histone HATs in the context of adipogenesis, wherein they play crucial roles in the activation of PPARγ and C/EBPα pathways [40,41]. In brown preadipocytes, the loss of GCN5/PCAF hinders adipogenesis by suppressing the expression of PPARγ and PRDM16, indicating the probable involvement of H3K9 acetylation in white adipose tissue browning [42].…”
Section: Discussionmentioning
confidence: 96%
“…For example, Yan Chen et al found that Lysine-Specific Demethylase 1 (LSD1) promotes adipocyte differentiation by demethylating H3K4 on promoter regions of WNT signaling components and repressing the WNT pathway [33]. Han-Heom Na et al reported that Tri-methylation level of H3K9 was decreased during adipocyte differentiation [34].…”
Section: Discussionmentioning
confidence: 99%
“…CBP and P300 are a functionally redundant HAT pair reported to acetylate H3K27 and are reported to be indispensable for adipocyte differentiation via activation of PPARγ [ 20 , 21 ]. Both these HATs’ expressions are induced during differentiation [ 22 ]. The reduced WAT level in cbp heterozygous mice suggests CBP’s critical role in white adipocyte differentiation [ 23 ].…”
Section: Histone Acetyltransferases (Hats)mentioning
confidence: 99%